Computational screening of fatty acid synthase inhibitors against thioesterase domain. Issue 15 (18th November 2018) - Panman, Wanwisa; Nutho, Bodee; Chamni, Supakarn; Dokmaisrijan, Supaporn; Kungwan, Nawee; Rungrotmongkol, Thanyada
Abstract : Thioesterase (TE) domain of fatty acid synthase (FAS) is an attractive therapeutic target for design and development of anticancer drugs. In this present work, we search for the potential FAS inhibitors of TE domain from the ZINC database based on similarity search using three natural compounds as templates, including flavonoids, terpenoids, and phenylpropanoids. Molecular docking was used to predict the interaction energy of each screened ligand compared to the reference compound, which is methyl γ-linolenylfluorophosphonate (MGLFP). Based on this computational technique, rosmarinic acid and its eight analogs were observed as a new series of potential FAS inhibitors, which showed a stronger binding affinity than MGLFP. Afterward, nine docked complexes were studied by molecular dynamics simulations for investigating protein–ligand interactions and binding free energies using MM-PB(GB)SA, MM-3DRISM-KH, and QM/MM-GBSA methods. The binding free energy calculation indicated that the ZINC85948835 (R34) displayed the strongest binding efficiency against the TE domain of FAS. There are eight residues (S2308, I2250, E2251, Y2347, Y2351, F2370, L2427, and E2431) mainly contributed for the R34 binding. Moreover, R34 could directly form hydrogen bonds with S2308, which is one of the catalytic triad of TE domain. Therefore, our finding suggested that R34 could be a potential candidate as a novel FAS-TE inhibitor for further drug design.